ESRA19-0565 National survey for the provision of anaesthetic ultrasound units in the UK. (30th August 2019) - Acres, N; Carter, P; Burckett-St Laurent, D
Abstract : Background and aims: Ultrasound-guided regional anaesthesia (UGRA) is utilised as both multi-modal analgesic and sole anaesthetic technique. UGRA offers opportunities for innovative care pathways to serve an increase in elderly and complex patients. The procurement of ultrasound remains an arduous task with little supportive evidence base. A survey was taken across Wales to offer an understanding of the actual and desired provision of ultrasound. Methods: The survey was built around similar parameters to National Audit Project 4. The National Hip Fracture Database was used to select 13 hospitals across Wales with CEPOD and trauma services. Questions included the presence of a regional lead, anaesthetic ultrasound services, actual and desired provision of ultrasound. Results: 45% of hospitals had a regional lead. A range of anaesthetic ultrasound services were available throughout Wales. Not one hospital had a dedicated ultrasound unit for trauma or CEPOD. 64% of hospitals felt this was inadequate. The ratio of ultrasound to theatres was on average 1:5 with an average desired ratio of 1:2. 80% of hospitals felt the lack of US units adversely impacted patient care and list efficiency, 55% felt similarly about teaching and development of ultrasound services. Conclusions: Anaesthetic ultrasound services are dependent on the provision of modern, high resolution ultrasound. All but one hospital surveyed had less than the desired ratio of ultrasound machines to theatres, with patient care, teaching, research and service development adversely affected. We hope this survey serves as a pilot to a larger national survey with a position statement on provision and governance from our national anaesthetic associations.